Nighttime Home Blood Pressure in Children: Association with Ambulatory Blood Pressure and Preclinical Organ Damage. Issue 6 (12th April 2021) - Stambolliu, Emelina; Kollias, Anastasios; Bountzona, Ioanna; Ntineri, Angeliki; Servos, George; Vazeou, Andriani; Stergiou, George S.
Abstract : Supplemental Digital Content is available in the text. Abstract : This study aimed to investigate a novel technique for nighttime blood pressure evaluation using a home blood pressure (HBP) monitor in children and adolescents, in terms of association with ambulatory blood pressure (ABP) and preclinical organ damage. Children and adolescents (aged 6–18 years) referred for elevated blood pressure were evaluated with ABP (24 hours) and HBP monitoring during daytime (7 days, duplicate morning and evening measurements) and nighttime (automated asleep measurements for 3 nights with 3 hourly measurements/night; Microlife WatchBP Home N). Preclinical organ damage was assessed by echocardiographic left ventricular mass index, carotid intima-media thickness, carotid distensibility coefficient, and carotid-femoral pulse wave velocity. Ninety-one individuals were analyzed (mean age 13.3±2.8 years; 54 men; 17 with elevated ABP). There was a close association between daytime (awake) ABP and HBP (r=0.81/0.77, systolic/diastolic) and between nighttime (asleep) values (r=0.78/0.60) (all P <0.05). Daytime HBP was slightly lower than daytime ABP (difference, −2.0±6.5/−0.9±5.1 mm Hg, systolic/diastolic, P <0.01/NS), whereas nighttime HBP was slightly higher than nighttime ABP (2.6±7.2/2.2±6.1 mm Hg, P <0.01 for both). Nighttime systolic ABP and HBP were correlated with left ventricular mass index (r=0.37 and 0.29, respectively), carotid intima-media thickness (0.45, 0.47), carotid distensibility coefficient (−0.22, −0.20), and carotid-femoral pulse wave velocity (0.47, 0.53) ( P =NS for comparisons between methods). The agreement between nighttime HBP and ABP in identifying individuals with nighttime hypertension (≥95th percentile for nighttime ABP) was 82% (κ=0.49; P <0.01) and nondippers 57% (κ=0.19; P =0.03). In conclusion, in children and adolescents, nighttime HBP monitoring is feasible, is closely associated with nighttime ABP and similarly associated with preclinical organ damage.